Influenza vaccination landscape in Italy: A comprehensive study through the OBVIOUS project lens - Angelo Capodici; Marco Montalti; Giorgia Soldà; Aurelia Salussolia; Giusy La Fauci; Zeno Di Valerio; Francesca Scognamiglio; Maria Pia Fantini; Anna Odone; Claudio Costantino; Heidi J. Larson; Julie Leask; et al. (Taylor & Francis Group, 2023)
Influenza annually claims an estimated 8,000 lives in Italy. Despite no-cost vaccinations for high-risk groups, hesitancy persists. This study aims to pinpoint social and behavioral vaccination determinants, forming strategies to bolster vaccine uptake. From April 11 to May 29, 2022, we surveyed a demographic-stratified sample of 10,000 Italian adults, employing the WHO's Behavioral and Social Drivers of Vaccination (BesD) framework. Of those, 4,613 (46.1%) were eligible for the influenza vaccine and included in the analysis. Roughly a third remained unvaccinated and unwilling. Central Italy showed the highest resistance, with significant percentages of seniors and professionals like teachers, law enforcement, and healthcare workers expressing noncompliance. A lack of awareness of being in a target group correlated significantly with vaccine refusal or delayed acceptance. Other refusal factors included female gender, being aged 45-54, rural residency, absence of higher education, perceived vaccine unsafety, and having vaccine-opposed acquaintances. Thus, addressing these perceptions and enhancing awareness can potentially increase vaccination rates and lessen disease impact.